Service Science in China - Huo, Jiazhen. (Springer Berlin Heidelberg : Imprint: Springer, 2013)
A service economy era is coming! As the basic discipline of the new service dominant era, service science mainly studies common rules of service activities, aiming to provide theoretical bases for creating future service value. This book, which integrates service management, operational management, logistics and supply chain management, presents a research system for this emerging discipline. This system consists in service philosophy, resource allocation, operational management and service technology. Many concrete cases involving Chinas service enterprises are incorporated into the book, in the hope of providing readers insights into not only service science but also the development of Chinas service economy.